Weak decays of hadrons reveal compositeness of quarks - de Souza, Mário Everaldo (Scientia Plena, 2011)
Considering the latest available data from the Particle Data Group this work shows that leptonic, semileptonic and nonleptonic weak decays of hadrons reveal the compositeness of quarks and provides a reasonable explanation for the apparent null results of quark compositeness and argues that, actually, primons (prequarks) have already been found by some important experiments such as EMC, SMC, SLAC E143 and HERMES.